2020
DOI: 10.1017/s0007114520002913
|View full text |Cite
|
Sign up to set email alerts
|

The rationale for a multi-step therapeutic approach based on antivirals, drugs and nutrients with immunomodulatory activity in patients with coronavirus-SARS2-induced disease of different severities

Abstract: In December 2019, a novel human-infecting coronavirus, named SARS-CoV-2, has been recognized to cause a pneumonia epidemic outbreak with different degree of severity in Wuhan, Hubei Province in China. Since then this epidemic spread worldwide in Europe, and Italy also have been involved. Effective preventive and therapeutic strategies are absolutely required to block this serious public health concern. Unfortunately, few studies about SARS-CoV-2 concerning its immunopathogenesis and treatment are available. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 111 publications
0
19
0
1
Order By: Relevance
“…The production of VD stimulated by sun radiation seems very effective in reducing viral infectivity and in preventing the development of more severe forms of viral-related infections. Therefore, its use has been proposed several months ago with a therapeutic or preventive role in patients at a higher risk of severe clinical manifestations of SARS-CoV-2-related infection, such as aged people or for the treatment of these individual [17,22,[210][211][212]. Whether solar radiation can be effective for viruses inactivation and for VD production, air pollution could severely prevent such beneficial effects, because airborne particles shield solar radiation up to significant levels [213].…”
Section: Considerations On the Possible Involvement Of Climatic Factors In Increasing The Risk Of Sars-cov-2 Spreadingmentioning
confidence: 99%
See 3 more Smart Citations
“…The production of VD stimulated by sun radiation seems very effective in reducing viral infectivity and in preventing the development of more severe forms of viral-related infections. Therefore, its use has been proposed several months ago with a therapeutic or preventive role in patients at a higher risk of severe clinical manifestations of SARS-CoV-2-related infection, such as aged people or for the treatment of these individual [17,22,[210][211][212]. Whether solar radiation can be effective for viruses inactivation and for VD production, air pollution could severely prevent such beneficial effects, because airborne particles shield solar radiation up to significant levels [213].…”
Section: Considerations On the Possible Involvement Of Climatic Factors In Increasing The Risk Of Sars-cov-2 Spreadingmentioning
confidence: 99%
“…It may reach the neurons of the brain, the heart, the spleen, the lymph nodes and other lymphoid tissues [15]. In particular, the SARS-CoV-2 infects the host's lymphocytes and macrophages, causing both their death through apoptosis and subsequent severe lymphopenia and, afterward, making them very efficacious carriers for its spreading [16,17]. Therefore, this virus reaches the mucosa-associated lymphoid tissue, bronchus-associated lymphoid tissue and nasopharynx-associated lymphoid tissue.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The lipid-soluble vitamin D needs magnesium to assume its active form (1,25[OH]2D)[ 45 ]. More and more studies have shown a link between low levels of vitamin D and increased susceptibility to contracting the SARS-CoV-2 infection, and in the severity of the clinical course[ 46 , 47 ]. In a recent meta-analysis, which included six studies[ 31 , 48 - 52 ] with a total of 5884 hospitalized COVID-19 patients, Hariyanto et al [ 53 ] showed how the use of PPIs was significantly associated with an increased risk of severity and mortality in COVID-19 cases.…”
Section: Introductionmentioning
confidence: 99%